(untitled) (Informatica, 2018)
Most genomic data studies are based on sequence comparisons and searches, and comparison models based on alignment algorithms are most commonly used. This method is very accurate, but it is useful when the query is short in kilobytes, because it requires the quadratic time and space complexity, O(n2) where n is the length of target and query sequences. With the development of Next Generation Sequencing techniques, researches on whole genome sequence data of megabyte size are being actively studied, and new comparison and search methods for large-scale sequence data are needed. We propose a new alignment-free sequence comparison and search method to overcome the limitations of the alignment-based model. In this graphical model, the sequence searching problem in DNA strings can be reduced to find some parts of geometric object within a relatively small-scale geometric space. When comparing similarity by modifying sequences of similar length, we can confirm that the comparison model is appropriate by accurately reflecting the degree of similarity. When searching the query sequence comparison model based on 200MB sized whole genome sequence, using the compressed coordinate information, it was able to search the 10MB sequences in 22s, which is a very reduced time compared to alignment. Although it is not possible to find the exact position of the base pair unit as in the alignment result, it is a model that can be used as a preprocessing process to quickly search a whole genome sequence of several hundred megabytes-size.